Ayushman Bharat Digital Mission and Public Health Transformation in India: Trends, Challenges, and Future Directions - Prafulla, Amit; Ranjan, Dr. Amit (International Journal of Aquatic Research and Environmental Studies, 2025)
The Ayushman Bharat Digital Mission (ABDM) is a transformative initiative aimed at modernizing India’s healthcare system through integrated digital health technologies. By promoting the adoption of electronic health records (EHRs), enabling real-time data interoperability, and supporting telemedicine services, by connecting fragmented health services into a unified digital ecosystem, ABDM seeks to streamline healthcare delivery by integrating digital tools that reduce costs, expand reach, and improve coordination of services for both providers and patients. This paper examines the evolving role of ABDM in shaping India’s public health infrastructure. It draws upon national implementation data from 2021 to 2025, including ABHA-linked EHR trends and the Digital Health Incentive Scheme (DHIS), while incorporating global best practices from the UK, Australia, and Estonia to contextualize India’s digital health journey. A mixed-methods approach is adopted, combining secondary analysis of government dashboards and policy documents with comparative case studies to assess the infrastructural, policy, and technological drivers of digital health transformation. Special focus is given to Bihar’s BHAVYA initiative, highlighting scalable, state-led models of EHR adoption in low-resource settings. The study identifies implementation challenges such as digital infrastructure gaps, health workforce capacity, privacy concerns under the Digital Personal Data Protection Act (DPDP) 2023, and limited interoperability across digital health systems. Policy recommendations include strengthening public–private partnerships, enhancing digital health literacy, and integrating AI-powered clinical intelligence into ABDM’s roadmap. The paper concludes that ABDM represents more than a technology platform - it is a national blueprint for digital health transformation aligned with the National Digital Health Blueprint (NDHB) 2019, offering replicable lessons for other low- and middle-income countries.